2017
DOI: 10.1089/jop.2016.0124
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Leukemia Virus Type 1 and Eye Diseases

Abstract: Human T cell leukemia virus type 1, also known as human T lymphotropic virus type 1 (HTLV-1), is a retrovirus that encodes a reverse transcriptase, which translates viral RNA into a DNA provirus that is integrated into the host genome. The virus was found to be a causative agent of adult T cell leukemia/lymphoma (ATL) in the early 1980s, and was also found to cause the neurological disorder tropical spastic paraparesis (TSP)/HTLV-1-associated myelopathy (HAM) and the inflammatory disorder HTLV-1 uveitis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…The peak age at uveitis onset was in the 50s followed by the 60s for women, and in the 60s followed by the 70s for men, according to one recent survey (Terada et al, 2017b), which showed that age at onset had increased compared with previous research. Women greatly outnumbered men among HU patients (Takahashi et al, 2000;Terada et al, 2017a). Recurrence of uveitis was seen in 30-50% of HU patients (Nakao and Ohba, 1993;Takahashi et al, 2000;Terada et al, 2017a).…”
Section: Htlv-1 Uveitismentioning
confidence: 95%
See 4 more Smart Citations
“…The peak age at uveitis onset was in the 50s followed by the 60s for women, and in the 60s followed by the 70s for men, according to one recent survey (Terada et al, 2017b), which showed that age at onset had increased compared with previous research. Women greatly outnumbered men among HU patients (Takahashi et al, 2000;Terada et al, 2017a). Recurrence of uveitis was seen in 30-50% of HU patients (Nakao and Ohba, 1993;Takahashi et al, 2000;Terada et al, 2017a).…”
Section: Htlv-1 Uveitismentioning
confidence: 95%
“…Women greatly outnumbered men among HU patients (Takahashi et al, 2000;Terada et al, 2017a). Recurrence of uveitis was seen in 30-50% of HU patients (Nakao and Ohba, 1993;Takahashi et al, 2000;Terada et al, 2017a).…”
Section: Htlv-1 Uveitismentioning
confidence: 95%
See 3 more Smart Citations